KEMAMPUAN PEDAGOGIK GURU DALAM MENGEMBANGKAN MATERI PENDIDIKAN AGAMA ISLAM SEKOLAH DASAR - Dewi Gita; Andi Anirah; Elya Elya; Andi Ardiansyah (PGMI Department of Universitas Islam Ibrahimy Banyuwangi, Indonesia, 2025)
The skill of educators in SD Inpres Donggala Kodi to create resources for Islamic Education in the 4th grade is essential for improving pupils' knowledge and regard for Islamic principles. The goal of this research is to analyze the educator's capability to create materials for Islamic Education in the 4th grade at SD Inpres Donggala Kodi, with a specific concentration on the subject of